Sharia and Economic Equity: An Empirical Study of Income Inequality in the Organization of Islamic Cooperation - Gunawan, Devina (Journal International Economic Sharia, 2024)
Objective; This study aims to explore the relationship between Sharia principles and economic equity, focusing on income inequality among member states of the Organization of Islamic Cooperation (OIC).Methods; Employing a quantitative approach, the research analyzes income distribution data from OIC countries over the past two decades. Multiple regression analysis is utilized to examine the impact of Sharia-compliant policies on income inequality, controlling for factors such as economic growth, education, and governance.Results; The findings indicate a significant negative correlation between the implementation of Sharia-compliant financial practices and income inequality levels within OIC countries. Specifically, countries that adhere more closely to Sharia principles demonstrate lower income disparities, suggesting that such practices may promote economic equity.Novelty; This study contributes to the literature by providing empirical evidence linking Sharia compliance with reduced income inequality, a relationship that has been underexplored in existing research.Research Implications; The results have important implications for policymakers within OIC member states, highlighting the potential for Sharia-compliant economic policies to enhance equity and foster inclusive growth